ANALISIS KEPUASAN PENGGUNA LULUSAN TERHADAP LULUSAN PRODI MANAJEMEN INDUSTRI KATERING - Dafina Fadila, - (2021)
The Catering Industry Management Study Program continues to be able to improve primary education because the results of primary education can produce quality and well-absorbed graduates in the world of work. Because when graduates are well absorbed by the market then college will get a positive assessment. One of those attempts was to conduct a user satisfaction survey aimed at determining the level of user satisfaction with the performance of the Katering Industry Management graduation. The method in this study uses descriptive research methods with quantitative approaches. The data collection used in this method is a survey method. Survey method is a research method that uses the main input to collect its data by spreading the quantum angle. The data processing technique uses the Consumer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods, which are a tool to analyze and compare the results of a satisfactory service to the expected seven aspects of the satisfaction of the licensee, namely integrity, team skills, Information technology, leadership, adaptation, communication, professionalism and English skills. In addition, there is a recommendation from the licensee on the management of the study program that: conduct soft skills and hard skills training according to its field and what knowledge material needs to be enhanced from the Indonesian University of Education's Katering Industry Management.